ANALISIS BENTUK FUNGSI DAN MAKNA WACANA CORONA VIRUS VERSI BAHASA INGGRIS (SUATU TINJAUAN PRAGMATIK) - Edward Edward; Sorta Hutahaean (Universitas Lancang Kuning, 2022)
This research was aimed at describing the types of forms and meanings found in the documentary text of the current cyber paper on coronavirus. The result shows that texts tend to be representative, and out of 32 data, only one was in the form of declarative, three directives, four commissives, and the rest were representatives. Meaning and form were determined by context and co-text. It can be concluded that the meaning is context-dependent but the structure varies accordingly. Some may have compound, comples, compound-complex, and even transformative sentences. In short, the context influences the whole text. It was found that exospheric context or reference was greatly influencing the meaning of the text.